Did Indian Equity Mutual Funds Use Derivatives to Hedge Their Exposure During COVID? - Krishnamurthy, Jaishankar; Singh, Satyendra Pratap (Indian Journal of Research in Capital Markets, 2024)
Purpose : The study examined the use of derivatives by mutual funds (MFs) to manage risks during COVID-19. We analyzed data of all MFs (excluding Arbitrage Funds) with equity exposure from the NAV, India database. Methodology : The authors reviewed over 500 equity MFs with assets under management of INR of 15 lakhs crores. They analyzed the derivative holdings of MFs from January 2019 to December 2023 to study the use of derivatives during pre-COVID, COVID-19, and post-COVID periods. The review examined which MFs used derivatives to hedge exposure and their performance versus their peers and benchmarks. The methodology used was the t-test, F-test, Levine’s test, and ANOVA. Findings : The results revealed that the fund managers did not hedge a significant portion of their portfolio. The analysis revealed that the derivative holdings by fund managers decreased significantly during COVID-19 and increased after the end of the pandemic. MFs with derivatives holdings of more than 2% of the portfolio did not beat the benchmark indices. However, MFs that used derivatives had lower variance than their respective benchmark, providing higher returns for the same level of exposure to risk. Practical Implications : The research provided valuable insights into how equity MFs utilized derivatives to hedge their exposure for investors, fund managers, and regulators, as well as highlighting the potential risk-reduction benefits of this strategy. Originality : This was the first study on the use of derivatives by Indian Mfs.